Modern marvels [ the weird and wonderful world of the everyday:corn and rats (New York : Actuality Productions Inc, 2008)
Corn has fed the masses from ancient times to this day. Its unique properties make it ideal for a number of applications. From packing material to plasticizers to fuel, corn is not only a vegetable and cereal grain, it is a vital comodity. Visit Lakeside Foods in Reedsburg, Wisconsin and see how tons of corn are harvested and canned within hours. Then to VeraSun Energy in Charles City, Iowa, to discover how corn is
Originally broadcast as episodes of the television series Modern marvels on the History Channel in 2007 and 2008
Produced by Actuality Productions, Inc. ;executive producer Michael Stiller; camera, Keith Barefoot ... [et al.] ; editor, Lou LaProcido ; music, Guy Thomas;writer/producer, Gloria L. Morris;writer/producer, Kaylan Eggert
Narrator, Max Raphael
Closed captioned
Keywords: Alcohol as fuel; Corn; Corn as food; Corn products; Corn -- Biotechnology; Corn -- History; Corn -- Processing; Corn -- Technological innovations; Genetically modified foods; Hybrid corn; Rats; Rats as laboratory animals; Rats as pets; Rats -- Control